Foreclosure of the principal residence and insolvency proceedings of a natural person who is not an entrepreneur (Acta Judicial Journal, 2021)
We will analyze in this work the different hypotheses that can be raised in the event of foreclosure of the habitual residence and the simultaneous or subsequent insolvency procedings of the natural person.